Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Determine if [tex](y-1)[/tex] is a factor of [tex]y^3 - 9y^2 + 10y + 5[/tex].

A. Yes
B. Not enough information to determine
C. No
D. Only if [tex]x=-1[/tex]


Sagot :

To determine if [tex]\((y-1)\)[/tex] is a factor of the polynomial [tex]\(y^3 - 9y^2 + 10y + 5\)[/tex], we can use the Factor Theorem. The Factor Theorem states that [tex]\((y-c)\)[/tex] is a factor of a polynomial [tex]\(P(y)\)[/tex] if and only if [tex]\(P(c) = 0\)[/tex].

Here, we need to check if [tex]\((y-1)\)[/tex] is a factor, which means we need to determine if [tex]\(P(1) = 0\)[/tex] for the polynomial [tex]\(P(y) = y^3 - 9y^2 + 10y + 5\)[/tex].

1. Substitute [tex]\(y = 1\)[/tex] into the polynomial:

[tex]\[ P(1) = (1)^3 - 9(1)^2 + 10(1) + 5 \][/tex]

2. Calculate each term:

[tex]\[ (1)^3 = 1 \][/tex]
[tex]\[ -9(1)^2 = -9 \][/tex]
[tex]\[ 10(1) = 10 \][/tex]
[tex]\[ 5 \text{ is a constant term} \][/tex]

3. Sum the calculated values:

[tex]\[ P(1) = 1 - 9 + 10 + 5 \][/tex]

4. Perform the arithmetic:

[tex]\[ P(1) = 1 - 9 + 10 + 5 = 7 \][/tex]

Since [tex]\(P(1) = 7\)[/tex] is not equal to 0, [tex]\((y-1)\)[/tex] is not a factor of the polynomial [tex]\(y^3 - 9y^2 + 10y + 5\)[/tex].

Therefore, the correct answer is:
C. No